Coupling Vibration Analysis of Turbine Shared Support Rotor-Bearing System with Squeeze Film Dampers - Jiaqi Han; Guihuo Luo; Wei Chen; Fei Wang; Lulu Liu; Zhenhua Zhao; Gang Luo (International Journal of Aerospace Engineering)
The turbine shared support structure is used widely in aeroengines, but theoretical and experimental research on a rotor-bearing system containing a shared turbine support structure is lacking. This paper reports research into the coupling vibration response of a squeeze-film-damper rotor-bearing system that has two spools with different rotation speeds and is supported by a turbine shared support structure. The problem is addressed by means of experimental tests and the finite-element method. Based on the features of a turboshaft engine with a turbine shared support structure, a rotor-bearing test system with a shared support structure and squeeze film damper is designed, and a finite-element model of the test system is built based on Timoshenko beam elements. The experimental and simulation results indicate that the unbalanced response of the rotor-bearing system with a shared support structure may involve either the sum or difference of the fundamental frequencies of the rotors of the gas generator and power turbine. The simulations show that the unbalance of the power turbine rotor, the radial and bending stiffnesses of the shared support structure, and the radial clearances of squeeze film dampers at the shared support structure of the rotor-bearing system all affect the coupling response. The amplitude of the coupling response can be suppressed effectively by (i) selecting reasonable parameter values for the turbine shared support structure and (ii) exerting strict control over the spool unbalance.